Republic of Latvia : Report on the Observance of Standards and Codes on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2007)
This report reviews the Observance of Standards and Codes on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for the Republic of Latvia. Latvia has taken strong measures in recent years, through legislative amendments and improvements in implementation, to address deficiencies in its AML/CFT framework and move closer to compliance with the Financial Action Task Force (FATF) Recommendations. Most of the necessary AML/CFT institutions and legal framework are now in place, although coverage of some designated nonfinancial businesses and professions (DNFBPs) is not yet complete.